STRATEGI KOMUNIKASI POLITIK DALAM PEMENANGAN KEPALA DAERAH PEREMPUAN DI KABUPATEN BEKASI - Siti Khodijah (Program Studi Ilmu Administrasi Negara, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam '45 (UNISMA) Bekasi, 2022)
Pemilukada is one of the instruments of political decentralization, which made possible the occurrence of a transfer of power from the centre to the area. Through representation and embodiment pemilukada popular sovereignty can be enforced. The election directly Head region and the Deputy Chief of The Bekasi Regency is one of the forms of democracy in 2012 has three pairs of prospective candidates in the Region and Deputy Head of the area’s competed in the election Districts in the Regency of Bekasi, (1) France Partner Hasan Yasin dan Rohim Minteraja, the couple on the stretcher from the 3rd parties; (2) Sa’dudin Couples and Jamal Lulail, carried from another party and 3; (3) couples M. Darip Jejen Mulyana and Sayuti, Carried from 7 party. Based on the final results of the General Election Commission’s recap of the Regencies in Jakarta, the head of the most votes and Deputy Chief of the Bekasi district won by pairs Neneng Hasanah Yasin and Rohim Minteraja (NERO). The focus of this research is to examine the factors that affect victory the win strategy and how NERO, with the formula issues (1) whats factors affect NERO’S victory; (2) How Political Communication Strategies do with 3 (three) basic concepts as the footing (1) Political Communication Strategies, (2) Political Participation and (3) Marketing of politics. The case study is done is with interviews and the collection of documents related to the winner in the election of Regional Heads NERO Regency of Bekasi. As the findings turned out to be a very decisive victory factor pair Neneng Hasanah Yasin with Rohim Minteraja i.e. the lights his father factor M. Yasin, who is one of the richest men in Regency of Bekasi, as well as supported businesses that work with teams either. The focus of this research is to examine the factors that affect victory the win strategy and how NERO, with the formula issues (1) whats factors affect NERO’S victory; (2) How Political Communication Strategies do with 3 (three) basic concept as the footing (1) Political Communication Strategies, (2) Political Participation and (3) Marketing of politics. The case study is done is with interviews and the collection of document related to the winner in the election of Regional Heads NERO Regency of Bekasi. As the findings turned out to be a very decisive victory factor pair Neneng Hasanah Yasin with Rohim Minteraja i.e the lights his father factor M.Yasin, who is one of the richest men in Regency of Bekasi, as well as supported businesses that work with teams either.